1 Effect of Conditioning, Rest, and Post-rest Transport Duration on Welfare Indicators of Beef Cattle Transported by Road. (8th October 2021) - Melendez, Daniela M; Marti, Sonia; Schwinghamer, Timothy D; Haley, Derek B; Schwartzkopf-Genswein, Karen S
Abstract: The aim of this study was to assess the effects of conditioning, rest, and post-rest transport duration on welfare indicators of 6–7 mo old beef calves. Three hundred and twenty-eight weaned calves (237 ± 29.7 kg BW) were randomly assigned to a 2 × 2 × 2 nested factorial design: conditioning, conditioned (C) or non-conditioned (N); rest, 0 (R0) or 8 (R8) h, and post-rest transport, 4 (T4) or 15 (T15) h. Calves were sampled prior to the first loading (L1), after 20h of transport, prior to and after the additional 4 or 15-h transport, and at 1, 2, 3, 5, 14, and 28 d after transport ended. Data were analyzed using the GLIMMIX procedure of SAS. Fixed effects included conditioning, transport and time nested within rest period, while random effects included animal and pen. Greater shrink (P < 0.01) was observed in C than N calves after the initial 20-h transport. The N calves had greater (P < 0.01) ADG than C calves between L1 and d 5, while C had greater (P < 0.01) ADG than N calves between 14 and 28 d. L-lactate concentrations and flight speed were greater (P ≤ 0.05) in C than N calves between L1 and d 5. The R8-T4 calves had greater (P < 0.01) ADG than R8-T15 calves between L1 and d 5. The R0-T4 calves had greater (P = 0.02) L-lactate concentrations than R0-T15 and R8-T4 calves on d 1. The R0 calves had greater (P < 0.01) ADG than R8 calves between 14 and 28 d. Preliminary results show physiological, behavioral, and performance differences across treatments, however, additional indicators are required to accurately assess the effect of conditioning, rest, and post-rest transport durations on calf welfare.